2002
DOI: 10.1007/s00114-001-0290-y
|View full text |Cite
|
Sign up to set email alerts
|

Midgut tissue of male pine engraver, Ips pini, synthesizes monoterpenoid pheromone component ipsdienol de novo

Abstract: For over three decades the site and pathways of bark beetle aggregation pheromone production have remained elusive. Studies on pheromone production in Ips spp. bark beetles have recently shown de novo biosynthesis of pheromone components via the mevalonate pathway. The gene encoding a key regulated enzyme in this pathway, 3-hydroxy-3-methylglutaryl-CoA reductase (HMG-R), showed high transcript levels in the anterior midgut of male pine engravers, Ips pini (Say) (Coleoptera:Scolytidae). HMG-R expression in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 25 publications
3
59
0
Order By: Relevance
“…Northern analysis showed that GPPS is up-regulated by JH III in a dose-and time-dependent manner in male thoraces, similar to the transcriptional pattern described for other mevalonate pathway genes involved in pheromone biosynthesis (data not shown) (19,36,37). Semiquantitative RT-PCR demonstrated that the expression of GPPS was predominately localized to the anterior midgut tissue of pheromone-producing male I. pini (Fig.…”
Section: Molecular Cloning and Sequence Analysessupporting
confidence: 80%
See 3 more Smart Citations
“…Northern analysis showed that GPPS is up-regulated by JH III in a dose-and time-dependent manner in male thoraces, similar to the transcriptional pattern described for other mevalonate pathway genes involved in pheromone biosynthesis (data not shown) (19,36,37). Semiquantitative RT-PCR demonstrated that the expression of GPPS was predominately localized to the anterior midgut tissue of pheromone-producing male I. pini (Fig.…”
Section: Molecular Cloning and Sequence Analysessupporting
confidence: 80%
“…Template DNA from an I. pini cDNA library in ZAP II (19) was amplified by using degenerate primers (5Ј-GTNGA-RATGYTICAYACN-3Ј; 5Ј-RTCRTCYTGIACYTGRAA-3Ј) designed to recognize E-IPPS cDNAs (30). Preliminary amplified products included a fragment corresponding to FPPS.…”
Section: Isolation and Cloning Of Gppsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tremendous progress of molecular methods during the past years and the availability of genome sequences of various model organisms shifted the interests of researchers more and more toward the genes involved in pheromone biosynthesis (14)(15)(16)(17)(18)(19)(20). Particularly, the use of RNA interference (RNAi)-mediated gene silencing and in situ RT-PCR has demonstrated the usefulness of these cutting edge tools for insect pheromone research, because they allow both the unequivocal assignment of gene function in vivo and cell localization of biosynthetic pathways within the organism (21)(22)(23).…”
mentioning
confidence: 99%